The Effectiveness of Learners Adopting YouTube and Webcomics as English Language Teaching (ELT) Materials - Muthmainnah Muthmainnah; Hasan Hasan; Ahmad Al Yakin; Supaprawat Siripipatthanakul Siripipatthanakul; Pongsakorn Limna Limna (Edumaspul: Jurnal Pendidikan, 2023)
Fully online language teaching is still a new approach in the Indonesian context, even though blended learning and technology have been integrated into English as a Foreign Language (EFL) classrooms for some time. The instructional design, YouTube and Webcomics (YouCom) as digital task-based language teaching (DTBLT) practices in synchronous and blended learning environments. The study investigates the effectiveness of learners adopting YouCom through determinants of engagement, motivation, cognitive process, and student satisfaction. It reflects what EFL students think about the difficulties faced by English majors when learning languages online through YouTube and Webcomic applications. The online survey was distributed to English learners in a university in Indonesia with 63 respondents through purposive sampling. The hypotheses were tested using multiple regression analysis (MRA). The results reveal that the cognitive process influences learners’ effectiveness, followed by student satisfaction, engagement, and motivation. The recommendation is to increase perceptions through the cognitive process, student satisfaction, and engagement because they are firmly and significantly associated with learners’ effectiveness. The expanded sample to other areas is suggested. The contribution could benefit educators in implementing English learners’ perceptions and increase their willingness to learn using Webcomics and YouTube as the teaching materials.